HUBUNGAN POWER OTOT LENGAN DAN BAHU DENGAN HASIL BELAJAR TOLAK PELURU PADA SISWA PUTRA KELAS VIII SMP NEGERI 6 RAMBAH (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: Based on the observations of researchers in class VIII SMP NEGERI 6 RAMBAH, the author also saw students lacking understanding of the techniques in shot putting, lacking or not meeting the Minimum Draft Criteria (KKM) given by Physical Education teachers. It is suspected that the arm and shoulder muscle strength of the eighth grade male students is still weak. Bullet weight used is 4 kg. The population is the entire subject of the study. The population in this study were all male students of class VIII SMP NEGERI 6 RAMBAH totaling 20 people. The sampling technique used is the random sampling technique, so the sample numbered 18 people. The instruments in this research are the arm and shoulder muscle power test and the bullet resistance capability test. Based on the results of research and data processing using statistical research procedures, it can be concluded that the relationship of variable X with variable Y obtained rcount = 0.732> rtable = 0.482 so there is a relationship between variable X and variable Y. Thus Ha is accepted. Hypothesis conclusions are accepted at α = 0.05 in other words there is a significant relationship between arm and shoulder muscle power towards learning outcomes of shot putting in male students of class VIII of SMP Negeri 6 RambahKey Words: Arm and Shoulder Muscle Power, Ability to Refuse Bullets